Nitric Oxide Metabolic Pathway in Drought-Stressed Nodules of Faba Bean (Vicia faba L.) - Chammakhi, Chaima; Boscari, Alexandre; Pacoud, Marie; Aubert, Grégoire; Mhadhbi, Haythem; Brouquisse, Renaud (International journal of molecular sciences, 2022)
Drought is an environmental stress that strongly impacts plants. It affects all stages of growth and induces profound disturbances that influence all cellular functions. Legumes can establish a symbiosis with Rhizobium-type bacteria, whose function is to fix atmospheric nitrogen in organs called nodules and to meet plant nitrogen needs. Symbiotic nitrogen fixation (SNF) is particularly sensitive to drought. We raised the hypothesis that, in drought-stressed nodules, SNF inhibition is partly correlated to hypoxia resulting from nodule structure compaction and an increased O2 diffusion barrier, and that the nodule energy regeneration involves phytoglobin–nitric oxide (Pgb–NO) respiration. To test this hypothesis, we subjected faba bean (Vicia faba L.) plants nodulated with a Rhizobium laguerreae strain to either drought or osmotic stress. We monitored the N2-fixation activity, the energy state (ATP/ADP ratio), the expression of hypoxia marker genes (alcohol dehydrogenase and alanine aminotransferase), and the functioning of the Pgb–NO respiration in the nodules. The collected data confirmed our hypothesis and showed that (1) drought-stressed nodules were subject to more intense hypoxia than control nodules and (2) NO production increased and contributed via Pgb–NO respiration to the maintenance of the energy state of drought-stressed nodules.